Fruit Salad - Macdonald, Roderick (Revue générale de droit, 2008)
In orthodox theory, the law of property is held to be fundamentally about the identification and protection of rights in things (corporeal property), assumed to be finite in space and infinite in time. But modern economies undermine the explanatory power of this orthodoxy four ways. First, the space of property can no longer be easily fixed once and for all. This is especially the case for incorporeals but is also true of corporeals. Second, the time of property is now understood differently. The past distinction between fruits and products has been questioned with the recognition that fruits, like products, can also diminish capital value. Third, the close association of fruits and revenues is becoming untenable. Many types of revenue actually represent the price of a partial alienation and can, consequently, be considered proceeds. Finally, developments both material (like genetic engineering) and intellectual (like moral rights) challenge the idea of property as a thing to use. While the theory of property in Book IV of the C.C.Q. continues to reflect traditional spatio-temporal assumptions, the law of secured transactions in Book VI rests on an alternative vision of property as value. This essay deploys a detailed analysis of the idea of fruits to illustrate how today the Civil Code balances distinctions between fruits, products and accessions (property as thing) on the one hand and between revenues, capital and proceeds (property as value) on the other.